Proliferative Activity in Libyan Breast Cancer with Comparison to European and Central African Patients - Boder, Jamela (Hindawi Publishing Corporation, 2013)
Background. We evaluated the relation of proliferative indices with clinicopathological features and prognosis in breast cancer (BC) of Libyan female patients. The data were compared with corresponding results in Finland and Nigeria. Patients and Methods. Histological samples of breast cancer from 130 patients were retrospectively studied. Mitotic activity index (MAI) and standardized mitotic index (SMI) were estimated. Results. There were statistically significant correlations between the proliferative indices and most clinicopathological features, with the strongest association observed for histological grade (P = 0.01 for SMI and P = 0.003 for MAI). The proliferative differences between Libyan, Nigerian, and Finnish population were prominent. The mean values of SMI and MAI in Libyan BC patients were 32.1 mitotic figures per square millimeter and 27.3 mitotic figures per 10 high-power fields, respectively. This is clearly lower than those in Nigeria but much higher than those in Finland. The differences between countries are seen in whole material and are also present in subgroups. The results indicated that mitotic activities can be reliable prognostic indicators in Libyan BCs, as they were among Finnish and Nigerian females. Univariate and multivariate analyses found at cut-offs of 19 and 44 mitosis/mm(2) of SMI were the most significant prognostic factors. Conclusions. Proliferative indices with careful estimation of the MAI and SMI could be applied as quantitative criteria for Libyan BC to separate the patients into good, moderate, and bad prognosis groups.